Antimicrobial and Antioxidant Activities of 18β-Glycyrrhetinic Acid Biotransformed by Aspergillus niger - Shaymaa Wagdy El-Far; Mahmoud A. Al-Saman; Fatma I. Abou-Elazm; Rania Ibrahim Shebl; Asmaa Abdella (Microbiology Research)
The search for novel plant-based antioxidant and antibacterial medication has garnered a lot of attention lately. Glycyrrhiza glabra, known as licorice, is one of the most important medicinal plants. The primary component of Glycyrrhiza glabra is glycyrrhizin, which is biotransformed into 18α- and 18β-glycyrrhetinic acid for a variety of medicinal purposes. The goal of this study was to improve the bioavailability of glycyrrhizin by its biotransformation into glycyrrhetinic acid by Aspergillus niger. The biotransformation process was optimized using response surface methodology. A two-level Plackett–Burman design was employed to identify the factors that had a significant impact on the process of biotransformation. The three main variables were pH, glycerrhizin concentration, and incubation time. These three medium components were further optimized using a 3-level Box–Behnken design, and their optimum levels were pH of 8, an incubation period of 6 days, and a glycyrrhizin concentration of 1%. Using these optimum conditions, the maximum level obtained was 159% greater than in the screening experiment. Regarding the antimicrobial activity of glycyrrhizin extract, Bacillus subtilis emerged as the most sensitive organism with the lowest MIC (60 µg/mL) and the highest zone of inhibition (17 mm). The most resistant organism was Pseudomonas aeruginosa, which had the highest MIC (400 µg/mL) and the smallest zone of inhibition (10 mm). In the case of glycyrrhetinic acid, Bacillus subtilis was the most sensitive organism with the highest zone of inhibition (32 mm) and the lowest MIC (20 µg/mL). Pseudomonas aeruginosa was the most resistant organism, with the lowest zone of inhibition (18 mm), and the highest MIC (140 µg/mL). The antioxidant activity of glycyrrhizin extract increased from 12.81% at a concentration of 63 µg/100 µL to 41.41% at a concentration of 1000 µg/100 µL, while that of glycyrrhetinic acid extract increased from 35.5% at a concentration of 63 µg/100 µL to 76.85% at a concentration of 1000 µg/100 µL. The present study concluded that biotransformation of glycyrrhizin into glycyrrhetinic acid increased its bioavailability and antioxidant and antimicrobial activities. Glycyrrhizin and glycyrrhetinic acid might be used as a natural antimicrobial and antioxidant in pharmaceutical industries